Supporting entrepreneurship and innovation - Crum, Janet; Hines, Samantha Schmehl (Emerald Publishing Limited, 2019)
Libraries have recently begun doing more to support entrepreneurship and innovation within their communities. Makerspaces and business incubators have become featured attractions in public and academic libraries and provide a unique way to reach out to a user group that can bolster a community in dynamic ways. In this volume of Advances in Library Administration and Organization, we delve beyond examples and case studies to look at how library leaders can develop support for innovation and entrepreneurship within their libraries and within the profession.Chapters include examinations of design thinking and space planning, staffing, mission statements, and makerspaces. The contributors to this volume cover libraries and their activities in North America, Europe and Africa, and also discuss professional development in entrepreneurship topics as well as support of innovation. Libraries are increasing support of entrepreneurship and innovation across the board, and this volume will position administrators and managers of libraries to better understand what's happening, and how to bring it into their own institutions.
Prelims -- Introduction: supporting entrepreneurship and innovation -- Tools for entrepreneurship and innovation -- Library activities related to entrepreneurship and innovation -- Case studies of libraries supporting entrepreneurship and innovation -- Innovation and entrepreneurship in library education -- About the authors -- Index.
Includes index.
Print version record
Keywords: Library administration -- Technological innovations; Library science -- Technological innovations; Entrepreneurship; Language Arts & Disciplines -- Library & Information Science -- Administration & Management; Library & information sciences